2016
DOI: 10.1074/jbc.m116.720656
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Membrane Disruption Pathways Are Induced by 40-Residue β-Amyloid Peptides

Abstract: Cellular membrane disruption induced by ␤-amyloid (A␤) peptides has been considered one of the major pathological mechanisms for Alzheimer disease. Mechanistic studies of the membrane disruption process at a high-resolution level, on the other hand, are hindered by the co-existence of multiple possible pathways, even in simplified model systems such as the phospholipid liposome. Therefore, separation of these pathways is crucial to achieve an in-depth understanding of the A␤-induced membrane disruption process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 57 publications
(86 reference statements)
6
69
0
Order By: Relevance
“…A number of other amyloidogenic polypeptides have been found to undergo lipid-induced aggregation coupled to membrane permeabilization, including islet amyloid polypeptide (IAPP) involved in diabetes [2, 19, 33] and Aβ peptide associated with AD neuropathology [14]. The results presented here imply that protein binding partners could also interfere with the aggregation of these polypeptides at the membrane surface.…”
Section: Discussionmentioning
confidence: 79%
“…A number of other amyloidogenic polypeptides have been found to undergo lipid-induced aggregation coupled to membrane permeabilization, including islet amyloid polypeptide (IAPP) involved in diabetes [2, 19, 33] and Aβ peptide associated with AD neuropathology [14]. The results presented here imply that protein binding partners could also interfere with the aggregation of these polypeptides at the membrane surface.…”
Section: Discussionmentioning
confidence: 79%
“…The key motif of Aβ peptides induces cellular membrane disruption, which has made it a potential target for pharmacological inventions recently [116118]. The kinetic and thermodynamic parameters of the dominant pathway of cellular disruption have been studied to be able to enhance pharmacological applications [119]. …”
Section: Peptide-peptide Interaction Driven Self-assemblymentioning
confidence: 99%
“…One recent single-molecular imaging study utilized sub-μM Aβ concentration and reported formation of small oligomers on membrane surfaces with restricted mobility, which might represent the nucleation step of Aβ in membrane-related environments [29]. A variety of membrane disruption effects have been observed in these model systems, including the leakage of liposome content [23,30], changes in membrane curvatures [31], lipid uptake [32] and vesicle fusion [33,34]. There may be a mixture of several different membrane disruption effects in a particular system.…”
Section: Introductionmentioning
confidence: 99%
“…It has been considered that the formation of ion channel might serve as a common mechanism in different types of amyloid diseases. In addition to the ion channel hypothesis, it has also been reported that large Aβ oligomers had the ability to fragmentize the lipid bilayers through detergent-like mechanisms, where the oligomeric cores were surrounded and stabilized by lipids [30,32]. Recently, it was suggested that the two processes might occur in steps, where the ion channels formed initially, and membrane fragmentation was induced at later stages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation